Electronics in New Music - Mahnkopf, Claus-Steffen (Hofheim Wolke Verlag, 2006)
Twelve artists—from composers to creators of sound installations—present their work in this volume. These pieces were all created in recent years, and represent the current state of technological options and their musical and artistic potential. Mark Applebaum, Sidney Corbett, Frank Cox, Georg Klein, Claus-Steffen Mahnkopf, Chris Mercer, Christoph Ogiermann, João Rafael, Alexander Stankowski, Steven Kazuo Takasugi, Ian Willcock, and Gerhard Winkler offer detailed analyses primarily of the technical aspects in relation to their respective poetic intentions.
Keywords: 21st Century (2001-2100); Electronic music